Well characterized 1019W cm2 operation of VULCAN - An ultra-high power Nd:glass laser - Danson, C; Collier, J; Neely, D; Barzanti, L; Damerell, A; Edwards, C; Hutchinson, M; Key, M; Norreys, P; Pepler, D; Ross, I; Taday, P; et al. (1998)
Peak intensities of 1019 W cm2 have been reliably obtained from a high power Nd:glass laser using chirped pulse amplification. An Additive Pulse Modelocked oscillator incorporating diode pumped Nd:LMA was used to generate the sub-picosecond pulse. The focal spot intensity distribution has been characterized in detail showing a three times diffraction limited beam.